Religiusitas dan Prokrastinasi Akademik Mahasiswa - Hayyinah, Hayyinah (Universitas Islam Indonesia, 2004)
This study examined the relationship between religiousity and academic procrastination. The proposed hypothesis is that there is a negative correlation between religiousity and academic procrastination. The data were collected using religiosity scale and academic procrastination scale. Subjects of this study were 86 college students from one private university in Yogyakarta, from various study discipline. The hypothesis was tested using Pearson product moment correlation. The study results show that there is a significant negative correlation between religiousity and academic procrastination ( r= -.748, p < 0.01). The more religious the student, the less procrastinator he/ she is in regard with his/ her academic activities.Key Words: Academic procrastination, religiousity